Facing problems of Restorative Justice in Portugal and Brazil: learning with/from the fields = Cómo hacer frente a los problemas de Justicia Restaurativa en Portugal y Brasil : aprender con/desde la práctica - Rego De Oliveira, Cristina (Revista de victimología, 2021)
Currently restorative justice for adults enforced by the Law n.º 21/2007, of 12 June, faces difficulties in Portugal and has a limited application (or no application at all). Rather the opposite tendency exists in Brazil: despite the absence of legal regulation, the restorative movement seems to be expanding. Starting from this difference, this article aims to uncover the institutionalization processes of restorative justice, arguing that it can be useful to (re)think the model adopted by those countries and learning from their lessons. On the one hand, the article reflects on several issues that can be associated with the failure of practices in Portugal, such as: a) the restrictive legal framework; b) the protagonists and the roles they played during the creation of these top-down models On the other hand, it is important to understand the hegemonic model adopted in Brazil in order to identify the risks to the principles and values that restorative practices face, such as their cooptation by political interests that do not put victims, offenders and community at the center of restorative justice.